Malassezia infection associated with stucco keratosis - Zhan Zhou; Jiali Zhu; Bin Jiao; Songgan Jia; Yanping Jiang (Medical Mycology Case Reports, 2024)
We report a case of a 20-year-old young woman with a large stucco keratosis in the mons veneris, one of the clinical variants of Seborrheic keratoses (SKs). Periodic acid-Schiff staining revealed a large number of Malassezia spores in the stratum corneum. After oral antifungal treatment with itraconazole for 4 weeks, the benign tumor was completely cleared without residue or recurrence, which may open a new perspective for exploring the pathogenesis of SKs.